Finite Time Thermodynamic modelling of a multi-fuel engine with producer gas from various biomass feedstocks. (1st February 2023) - Percy, A. Jemila; Edwin, M.
Highlights: The theoretical prediction was made using Finite Time Thermodynamic (FTT) modelling. Rubber shell operated multi fuel engine shows the highest BTE of 20.18%. Lowest diesel consumption of 0.27 kg/h has been reported for dual fuel mode. Minimum equivalence ratio of 0.67 was observed for the rubber shell fuelled engine. Abstract: In this work, the theoretical prediction was made on the performance characteristics of a dual fuel engine utilizing Producer gas (PG) generated from Rice husk (RH), Coconut shell (CS) and Rubber shell (RS) as secondary fuels. The theoretical prediction was made using Finite Time Thermodynamic (FTT) modelling of an air standard dual cycle for diesel PG operation. Output characteristics such as Brake Thermal Efficiency (BTE), fuel consumption and equivalence ratio for a 3.75 kW lab scale multi-fuel engine by varying the engine load (20–80 %) and compression ratio (14–18) were experimentally measured and theoretically predicted. The RS-operated engine showed the highest BTE of 20.18 % at CR of 18 and at 80 % load, the lowest diesel consumption of 0.27 kg/h at CR of 14 and 20 %Load, and the lowest equivalence ratio of 0.21. At 80 % load and CR of 18, the CS-derived system showed a slight increase in BTE as 19.26 %, and the minimum diesel consumption (1.6 kg/h) and equivalence ratio (0.29) were obtained at CR14 and 20 % load. However, at 80 % load and CR of 18, the RH-powered engine showed the least BTE of 18.54 %, maximum diesel consumption of 0.81 kg/h, and maximum equivalence ratio as 0.75. The values obtained using theoretical predictions using FTT are closely relevant to the experimental results. Hence FTT based modelling of a dual fuel engine can be used as an effective tool for performance prediction of a dual fuel engine using PG generated from biomass sources in isolated regions.